Aquaculture's visual culture scientific documentation and the transformation of freshwater - Remetir, Trisha Federis (Philippine Studies: Historical and Ethnographic Viewpoints, 2023)
The 1970s rise of aquaculture sparked rapid scientific, social, and ecological transformations in Philippine freshwater landscapes. During this period aquaculture research institutions used film cameras to document breakthroughs in fish farming, which were later published in annual reports and documentaries. This article focuses on the role of visuality in aquaculture's historical rise. It argues that the research institutions' photographs of Laguna de Bay, in the 1970s and 1980s reveal a desire to recast freshwater sites as efficient spaces for fish production. Using a visual studies framework, it reveals how aquaculture research institutions were not just observers but also active participants in the transformation of freshwater landscapes.